2012
DOI: 10.3354/meps09299
|View full text |Cite
|
Sign up to set email alerts
|

Seabird diet indicates changing Arctic marine communities in eastern Canada

Abstract: Changing climatic conditions are affecting ecosystems worldwide, but polar ecosystems are experiencing the most rapid changes as the extent of summer sea ice has diminished over the last several decades. In the Canadian Arctic, thick-billed murres Uria lomvia can be used as samplers of the marine environment, and we examined changes in the diet of the birds between recent and historical studies from the 1970s and 1980s. In the low Arctic, the amount of Arctic cod, an ice-dependent species, declined in the murr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 26 publications
5
69
2
Order By: Relevance
“…In addition, Chambellant et al (2013) found that the importance of Arctic cod to ringed seal diet declined after 2000 in western Hudson Bay, while capelin and sand lance became more prevalent thereafter. Similarly, several sea bird populations in Hudson Bay have switched from an Arctic-cod-dominated diet to capelin since the late 1990s (Gaston et al 2003;Provencher et al 2012). Overall, ringed seals, as a species, employ dietary plasticity to changing resource availability and environmental conditions.…”
Section: Temporal Variationmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Chambellant et al (2013) found that the importance of Arctic cod to ringed seal diet declined after 2000 in western Hudson Bay, while capelin and sand lance became more prevalent thereafter. Similarly, several sea bird populations in Hudson Bay have switched from an Arctic-cod-dominated diet to capelin since the late 1990s (Gaston et al 2003;Provencher et al 2012). Overall, ringed seals, as a species, employ dietary plasticity to changing resource availability and environmental conditions.…”
Section: Temporal Variationmentioning
confidence: 97%
“…The physical factors affecting the Arctic climate are in extreme states, with no indication that a reversible shift will occur in the foreseeable future (Hinzman et al 2013;Polyakov et al 2013). These marine environmental changes are dramatically altering habitat (Laidre et al 2008) and causing a higher prevalence of subarctic species (Higdon and Ferguson 2009;Provencher et al 2012) and parasites/disease (Davidson et al 2011), which have together negatively impacted the abundances and distributions, decreased the growth and condition, and changed the behavior of numerous Arctic organisms, ranging from phytoplankton to polar bears (Wassmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this TS, Burthe et al (2012), Pro - Watanuki et al (2012), Grémil-let et al (2012), and Dorresteijn et al (2012) show how seabird food webs are changing in different regions. The changes in food webs, exemplified by changes in seabird diet, sometimes (Burthe et al 2012) but not always (Dorresteijn et al 2012, Grémil-let et al 2012, Provencher et al 2012, Watanuki & Ito 2012 reflect changes in diet quality; often the food web change is driven by species abundance or availability (Dorresteijn et al 2012). In some cases, these changes affect breeding success or other demographic attributes.…”
Section: Disparate Mechanisms Of Responsementioning
confidence: 99%
“…Studies that have examined the diet of Thick-billed Murres have been ongoing in Canada since the 1970s, and recent work has shown that changing climatic conditions are affecting the forage fish species in the region (Gaston et al, 2003). Declining levels of summer sea ice are linked with a decline in ice-associated Arctic cod (Boreogadus saida) and an increase in the warmer water capelin (Mallotus villosus) in the diet of the murres in the low Arctic region, where summer sea ice has declined the most (Provencher et al, 2012).…”
Section: Identifying Changes In Northern Food Websmentioning
confidence: 99%
“…Collaborative community research efforts and education opportunities related to marine bird research continue to provide insight and capacity building with our northern partners (Mallory et al, 2006a;Provencher et al, 2013). Marine birds also offer long-term data sets that are helping us to understand how changing conditions may be affecting wildlife throughout the region (Provencher et al, 2012;Iverson et al, 2014). Through my own PhD research and as a member of the northern marine bird research team, I strive to carry on this collaborative approach to northern research, always keeping in mind that those who study birds in the North are more than just bird biologists.…”
Section: Identifying Changes In Northern Food Websmentioning
confidence: 99%